Developing prospective mathematics teachers’ knowledge of the modelling approach - Shahbari, Juhaina Awawdeh; Tabach, Michal (Scientia in educatione, 2018)
Modelling is considered an important approach that requires prospective teachers to be qualified both in modelling competencies and in pedagogical knowledge. In order to investigate the development of these competencies, we examined 49 prospective mathematics teachers studying in a course that included a sequence of modelling activities. During the course, groups of 5–6 participants engaged in these modelling activities as learners. The data include two sets of reports by the prospective teachers on their observations of a recorded modelling activity carried out by a group of five 6th grade students. The first set of reports was collected before the prospective teachers worked on any modelling activities, while the second set was collected after they had engaged in the modelling activities. The findings indicate that, prior to working on modelling activities, most of the prospective teachers described the students’ modelling activity as a linear process and focused on the final mathematical model and the mathematical results. After the prospective teachers engaged in the activities, most of their reports identified cyclical processes as the mathematical models progressed.